Longterm experience of magnerot administration in patients with mitral valve prolapse - A. I. Martynov; E. V. Akatova (Евразийский Кардиологический Журнал, 2011)
Within 15 years observation 31 patients with prolaps the mitral valve, regularly accepting magnerot, in a dose of 1500 mg a day during all period of observation by 3-month's courses 2 times a year was spent. Features of dynamics of a clinical picture, their interrelation with phenotypic expression of a dysplasia of a connecting tissue, changes of an electrocardiogram, a structure of the valves apparatus of heart, a condition of a vegetative homeostasis, change of level and a daily profile of arterial pressure, a tonus of sympathetic and parasympathetic departments of vegetative nervous system are taped. Against treatment according to the retrospective analysis significant improvement of clinic-tool indicators at all surveyed patients isn't. After regular application of magnesium salt orotate acids authentic improvement of quality of life at patients with prolepses the mitral valve is established.